TACKLING THE TRANSNATIONAL THREAT OF HUMAN TRAFFICKING IN THE POST-COVID-19 PANDEMIC ERA: THE ROLE OF MALAYSIA AS THE ASEAN CHAIR - Michael , Sheila Devi (Malaysian Journal of International Relations, 2025)
Human trafficking remains a grave and persistent issue in Malaysia and across Southeast Asia, demanding urgent and coordinated action. Since the reopening of international borders following the COVID-19 pandemic, trafficking networks have swiftly adapted, employing advanced technologies, including artificial intelligence, to lure victims with fraudulent job opportunities, subsequently trapping them in exploitative online scam operations. Disturbingly, even Malaysians have fallen prey to these schemes and have been rescued by syndicates operating across the region. Child trafficking presents an equally pressing concern, with an alarming increase in cases involving vulnerable children, both from within and outside Southeast Asia, being subjected to sexual exploitation, forced labour, and coerced marriages. As the current Chair of ASEAN, Malaysia holds a critical leadership role in galvanising regional cooperation to address this transnational threat. The sophisticated tactics employed by modern traffickers necessitate an equally innovative, collaborative, and technology-driven response from governments, civil society organisations, and the international community.